Krisis Integritas Dan Lemahnya Supremasi Hukum Menjadi Ancaman Korupsi Terhadap Masa Depan Bangsa Indonesia - Teguh Wibowo; Irma Mangar (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2026)
Abstract: Law enforcement is a prerequisite for realizing legal protection in Indonesia. Law enforcement in Indonesia is a complex and ongoing issue, involving various structural, cultural, and political factors. Although Indonesia has a clear legal framework, the implementation of law enforcement often does not reflect the principles of justice and transparency. This research is a normative research. Normative legal research has a tendency to portray law as a prescriptive discipline where it only looks at law from the perspective of its norms which are of course descriptive. This research was conducted in real conditions with the aim of being able to find existing facts to be used as data filler in this research so that later the problem will be found. Implementation of the Supremacy of Law in Indonesia: Fact or Illusion that in the realization of law enforcement there are several obstacles, especially obstacles from the legal system itself. It is hoped that students are able to overcome and improve by channeling their aspirations in solving these obstacles. Students as academics must implement their actions to advance this country and represent the aspirations of the community because basically students uphold the interests of the community.